Oxidative Lactamization of Amino Alcohols: An Overview - Lakashima Sreerama; Esmail Vessally; Farnaz Behmagham (Journal of Chemistry Letters)
Lactams are essential functional groups in a number of pharmacologically and biologically active compounds. They are widely found in many natural products, marketed drugs, as well as in the base of polymeric structures (e.g., polyamides/Nylons). In this context, it is quite important to develop novel and efficient methods for the synthesis of these compounds. Recently, intramolecular dehydrogenative coupling reactions of amino alcohols, which generate only hydrogen as a side product, have emerged as one of the most versatile and powerful synthetic strategies to construct lactam rings. In the present review we will discuss recent advances on this chemistry with the emphasis on the mechanistic aspects of the reactions.